Experience, Confession, Statement: Gender and Identity Formation in Serbian Women’s Fiction (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The literary transformation of women’s experience springs from antagonistic and ambivalent attitudes towards artistic tradition and artistic practice, since the mediation of women’s experience calls for the reconstruction of those epistemological and interpretative norms and practices related to the making of a literary work. Afraid that her unique experience might be transformed into a cliche, a woman author is always asking the question of relevance – is the experience of a woman’s growing up and reaching maturity important enough to be fictionalized? The subject matter of women’s experience turns into a stumbling block due to awareness that literary tradition lacks a bold and resolute reconsideration of the plots dealing with female life and growth. The paper sets out to explore three novels by women authors released in 2014, discussing the issues of growth and maturity along with the topics of diversity, identity crises within a frame of a fluid text bearing resemblance to fragmentary novel, autobiography and a short story cycle.
Keywords: gender; literature; experience; formative influence; Serbian fiction